Hepatitis B Infection and Liver Transplantation - Eric M Yoshida (Canadian Journal of Gastroenterology)
Patients with chronic hepatitis B virus (HBV) infection have historically incurred high rates of allograft reinfection from extrahepatic reservoirs of HBV, with worse long term outcome compared with that of transplant recipients without HBV infection. As a result, chronic HBV infection has been considered a contraindication for transplantation. Prophylaxis against HBV recurrence, in the form of passive immunization with high dose hepatitis B hyperimmunoglobulin and the antiviral agent lamivudine, has recently been demonstrated to decrease the risk of reinfection. With appropriate prophylaxis, liver transplantation can be a viable proposition for patients with HBV infection. Past experience and current status of HBV infection and transplantation are reviewed, with emphasis on the issues surrounding prophylaxis.